Alzheimer’s disease-specific transcriptomic and epigenomic changes in the tryptophan catabolic pathway - Choe, Kyonghwan; Ali, Muhammad; Lardenoije, Roy; Riemens, Renzo J. M.; Pishva, Ehsan; Bickel, Horst; Weyerer, Siegfried; Hoffmann, Per; Pentzek, Michael; Riedel-Heller, Steffi; Wiese, Birgitt; Scherer, Martin; et al. (Alzheimer's research & therapy, 2024)
Neurodegenerative disorders, including Alzheimer’s disease (AD), have been linked to alterations in tryptophan (TRP) metabolism. However, no studies to date have systematically explored changes in the TRP pathway at both transcriptional and epigenetic levels. This study aimed to investigate transcriptomic, DNA methylomic (5mC) and hydroxymethylomic (5hmC) changes within genes involved in the TRP and nicotinamide adenine dinucleotide (NAD) pathways in AD, using three independent cohorts. DNA derived from post-mortem middle temporal gyrus (MTG) tissue from AD patients (n = 45) and age-matched controls (n = 35) was analyzed, along with DNA derived from blood samples from two independent cohorts: the German Study on Ageing, Cognition, and Dementia in Primary Care Patients (AgeCoDe) cohort (n = 96) and the Dutch BioBank Alzheimer Center Limburg (BBACL) cohort (n = 262). Molecular profiling, including assessing mRNA expression and DNA (hydroxy)methylation levels, was conducted using HumanHT-12 v4 Expression BeadChip and HM 450 K BeadChip arrays, respectively. Functional interactions between genes and identification of common phenotype-specific positive and negative elementary circuits were conducted using computational modeling, i.e. gene regulatory network (GRN) and network perturbational analysis. DNA methylation of IDO2 (cg11251498) was analyzed using pyrosequencing. Twelve TRP- and twenty NAD-associated genes were found to be differentially expressed in the MTG of AD patients. Gene sets associated in the kynurenine pathway, the most common TRP pathway, and NAD pathway, showed enrichment at the mRNA expression level. Downstream analyses integrating data on gene expression, DNA (hydroxy)methylation, and AD pathology, as well as GRN and network perturbation analyses, identified IDO2, an immune regulatory gene, as a key candidate in AD. Notably, one CpG site in IDO2 (cg11251498) exhibited significant methylation differences between AD converters and non-converters in the AgeCoDe cohort. These findings reveal substantial transcriptional and epigenetic alterations in TRP- and NAD-pathway-associated genes in AD, highlighting IDO2 as a key candidate gene for further investigation. These genes and their encoded proteins hold potential as novel biomarkers and therapeutic targets for AD.